(untitled) (Global Journal of Science Frontier Research, 2024)
This study investigated the contribution of fish farming to the socio-economic status of fish farmers in Ebonyi State Nigeria Multi-stage sampling techniques was used and 96 farmers were chosen at random Structured questionnaires were used to collect data which was then analyzed using descriptive statistics and multiple regression models The results of socio-economic characteristics revealed that the majority of fish farmers 82 3 were male married 62 5 well-educated and between the ages of 31 and 40 43 8 Benefits derived and constraints faced by farmers had a significant influence on their socio-economic status at p 0 025 and p 0 007 respectively The most significant constraints were the high cost of conventional fish feeds limited access to credit and the unavailability of fingerlings The study suggests that farmers be trained in feed formulation breeding and other farm management activities to boast production in the study area